2023
DOI: 10.3389/fvets.2023.1017001
|View full text |Cite
|
Sign up to set email alerts
|

Semi-quantitative risk assessment of African swine fever virus introduction in pig farms

Abstract: A semi-quantitative risk assessment was developed to classify pig farms in terms of the probability of introduction of African swine fever virus (ASFV). Following on-farm data collection via a specific checklist, we applied a modified failure mode and effect analysis (FMEA) to calculate the risk priority codes (RPC's), indicating increasing risk levels ranging from 1 to 5. The importance of biosecurity measures was attributed by experts. To consider geographic risk factors, we classified pig farms based on loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…The results showed that breeding/nursery farms totalized a higher mean biosecurity score than fattening farms, according to Silva et al [ 53 ] and Scollo et al [ 54 ], since these were most likely to undergo certification and annual monitoring by the official veterinary service. Moreover, breeding farms are at the top of the sanitary pyramid in pig production; they have a high sanitary status and a reduced risk of the introduction of pathogens [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that breeding/nursery farms totalized a higher mean biosecurity score than fattening farms, according to Silva et al [ 53 ] and Scollo et al [ 54 ], since these were most likely to undergo certification and annual monitoring by the official veterinary service. Moreover, breeding farms are at the top of the sanitary pyramid in pig production; they have a high sanitary status and a reduced risk of the introduction of pathogens [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…For data collection on farms, we used a checklist that was developed by Scollo et al [ 12 ] and contained 98 items, mostly with dichotomous answers. Eighteen new items were added to the original checklist to consider specific characteristics of outdoor farming.…”
Section: Methodsmentioning
confidence: 99%
“…Sub-criteria were assigned five-level importance scores by expert elicitation, with the collaboration of eight experts from countries affected by ASF, with experience in pig management and ASF control. The importance of the original 24 sub-criteria from [ 12 ] within the six main criteria was calculated using a modified Borda method [ 15 ]. During the evaluation of the sub-criteria by the expert panel, some of the items were considered of crucial importance for biosecurity against the introduction of ASFV in pig farms, and those were defined as critical items ( Table S1 in supplementary material ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations